A DFT study on functionalization of acrolein on Ni-doped (ZnO)6 nanocluster in dye-sensitized solar cells. Issue 12 (December 2019) - Dheivamalar, S.; Banu, K. Bansura
Abstract: In this work, the functionalization of Acrolein on the Nickel-doped Zn6 O6 (A-NiZn5 O6 ) nanocluster with different adsorption configurations (C, M1 & M2 ) as the π conjugated bridging in dye-sensitized solar cells (DSSC) compared with the anchoring group [6, 6] - phenyl-C61 -butyric acid methyl ester (PCBM) have been investigated through (DFT/TD-DFT)) calculations by Gaussian 09 program. The interaction between the NiZn5 O6 and the Acrolein has been explored through three functional groups are = O Carbonyl group (C), –CH Methyl group (M1 ), and –CH2 Methylene group (M2 ) of the Acrolein. The nature of the interaction between the Acrolein and NiZn5 O6 has been exhaustively studied in terms of energy gap (Eg ), global reactivity descriptors, molecular geometries, adsorption energy, the density of states, Mulliken atomic charges, molecular electrostatic potential, and the UV-Vis spectra for each adsorption site. The frontier molecular orbital analysis study indicated that all dyes could give a suitable electron vaccination from the LUMO orbital of A-NiZn5 O6 to the HOMO orbital of PCBM. The adsorption process significantly improved the incident photon to the current conversion potency of the A-NiZn5 O6. The determination of density functional theory calculations revealed that the C site of A-NiZn5 O6 material was faced with a lower chemical hardness and energy gap (Eg ) as well as a higher electron accepting power and light harvesting efficiency compared to other sites. Abstract : Materials chemistry; Nanotechnology; Optics; Theoretical chemistry; DSSC; NiZn5O6; DFT; Adsorption; Density of states